The structural analysis and interpretation of Sesotho folktale: Mokoko le Phakwe - Nthako, M. S. (University of the Free State, 2012)
Folktales are literally forms that reveal the soul of any society; they express its wishes, desires, hopes and beliefs about the world. They are often ancient, have fictitious characters and situations and mostly oral traditions before they were written down. According to the South African folklore journal, 'African folktales are in their very nature plain, and primitive in their simplicity; not adorned with the wealth of places and precious stones to be met with in the folklore of more civilized nations, but descriptive in great measure of the events of everyday life, among those in a low state of civilization; and with the exception of evidence of moral qualities, and of such imagery as is connected with the phenomena of nature , very little that is grand or magnificent must be looked for in it'. The central aim of this study is to indicate through Vladimir Propps's Morphological Analysis of Russian Folktales (1927) that African folktales, in this case Sesotho folktales, have much to look for with regard to Sesotho folktales, called'Mokoko le Phakwe' (The Cock & the Hawk) The analysis of this folktale will be considered within the Syntagmatic structural approach, where the text is described in chronological order as reported by the story teller , and within the Paradigmatic structured approach, where patterns underlying the folkloristic text is not a requested structure , but where elements are regrouped in a more analytical manner to manifest latent content within the text. It is this latent content that this study will employ to highlight the importance of oral literature to our daily lives, to highlight how Sesotho folktales can play a major role in the interpretation of socio-economic situations in the lives of African people even today.
Dissertation (M.A. (African languages))--University of the Free State (Qwaqwa Campus), 2012
Keywords: Sotho (African people) -- Folklore; Folklore -- Structural analysis; Folk literature, Sotho -- History and criticism; Animals -- South Africa -- Folklore